2023
DOI: 10.1038/s41419-023-05743-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA demethylation of the ZNF334 promoter inhibits colorectal cancer growth

Abstract: Colorectal cancer (CRC) is a leading cause of cancer deaths worldwide. Aberrant regulation of DNA methylation in promoters of tumor suppressor genes or proto-oncogenes is one of the fundamental processes driving the initiation and progression of CRC. Zinc-finger proteins (ZNFs) are one of the most abundant groups of proteins and function in many important biological processes related to tumorigenesis. Herein, we detected abnormal hypermethylation of the ZNF334 gene in CRC tissues compared with normal tissues, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…FLT3 has been identified as being overexpressed in hematologic malignancies, such as acute myelogenous leukemia ( Gilliland and Griffin, 2002 ). On the other hand, upregulation of ZNF334 has been associated with hepatocellular carcinoma (HCC), and triple-negative breast cancer (TNBC) ( Yang et al, 2023 ). This limited association suggests that it is necessary to do an exhaustive research in FLT3 and ZNF334 properties related to NSCLC and re-evaluate its impact in the disease development.…”
Section: Resultsmentioning
confidence: 99%
“…FLT3 has been identified as being overexpressed in hematologic malignancies, such as acute myelogenous leukemia ( Gilliland and Griffin, 2002 ). On the other hand, upregulation of ZNF334 has been associated with hepatocellular carcinoma (HCC), and triple-negative breast cancer (TNBC) ( Yang et al, 2023 ). This limited association suggests that it is necessary to do an exhaustive research in FLT3 and ZNF334 properties related to NSCLC and re-evaluate its impact in the disease development.…”
Section: Resultsmentioning
confidence: 99%
“…ZNF334 is a newly identified member of Zinc Finger Proteins (ZNFs), and over the last few decades, increasing evidence has supported key roles for ZNFs in cancer metastasis through regulating transcription of downstream genes, which are involved in proliferation, apoptosis, senescence, migration, and invasion [ 40 ]. The second selected down-regulated gene is TINAGL1 , an extracellular matrix protein that promotes integrin-mediated cell adhesion, whose expression is dependent on Sec.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al reported decreased expression of ZNF334 in breast cancer tissues and cell lines and showed that re-expression of ZNF334 in TNBC cell lines could suppress their growth and metastatic capacity [ 42 ]. Yang et al detected the downregulation of ZNF334 gene expression in the occurrence of colorectal cancer and defined it as a molecular marker for the early diagnosis of colorectal cancer [ 40 ]. Similarly, Sun et al clarified the effect of the ZNF334 deletion on the occurrence of hepatocellular carcinoma and described it as a molecular marker for liver cancer early diagnosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%